Quantum correlation-enhanced dual-comb spectroscopy - Zhuoren Wan; Yuan Chen; Xiuxiu Zhang; Ming Yan; Heping Zeng (Light: Science & Applications)
Abstract Dual-comb spectroscopy (DCS) is a powerful technique for spectroscopic sensing, offering exceptional spectral bandwidth, resolution, precision, and speed. However, its performance is fundamentally limited by quantum noise inherent to coherent-state optical combs. Here, we overcome this barrier by introducing quantum correlation-enhanced DCS using correlated twin combs generated via seeded four-wave mixing. One comb acts as a local oscillator to decode molecular signals, while the twin suppresses shot noise through intensity-difference squeezing, achieving a 2 dB signal-to-noise ratio improvement beyond the shot-noise limit—equivalent to a 2.6× measurement speed enhancement. Notably, when coupled with up-conversion spectroscopy, our technique records comb-line-resolved, high-resolution (7.5 pm) spectra in the critical 3 μm region for molecular fingerprinting. These results bridge quantum optics and frequency comb spectroscopy, offering great potential for trace gas detection, precision metrology, and chemical analysis. Future developments in detector efficiency and nanophotonic integration could further enhance its scalability and impact.